Surgical management of lateral ankle instability in athletes - Camacho, L. D.; Roward, Z. T.; Deng, Y.; Latt, L. D. (Journal of Athletic Training, 2019)
Ankle sprains are common injuries involving the lateral ankle ligaments and affect athletes of all levels. Most patients heal uneventfully, but those with symptoms persisting past 3 months should be evaluated for chronic ankle instability and its associated conditions as well as for the presence of varus malalignment. Chronic ankle instability is initially treated nonoperatively, with surgical management reserved for those who have failed to improve after 3 to 6 months of bracing and functional rehabilitation. Anatomic repair using a modification of the Broström procedure is the preferred technique for initial surgery. Anatomic reconstruction with tendon graft should be considered when repair is not possible, as it maintains physiological joint kinematics. Nonanatomic reconstructions are seldom indicated. Arthroscopic repair or reconstruction of the lateral ankle ligaments is a promising new technique with results similar to those of open surgery.